Metaphors Stemming from Nature in the Poetry of Mahmoud Darwish - Al-Sheikh, Nawal (Indonesian Journal of English Language Studies (IJELS), 2021)
This is a critical paper inspecting metaphors, the most artistic device, in Mahmoud Darwish's poetry. This research classified metaphors into three basic categories: metaphors of trees and plants such as wheat, metaphors of animals and birds such as butterfly, hoopoe, and dove, and metaphors of concrete and abstract natural elements. This study reports the fact that Darwish was brought up in a rural community. His father was a villager who grew crops for being food secure. Consequently, that rural environment affected the poetry of Darwish through metaphors and symbolism. Thus, it can be concluded that these poetic metaphors are a logic outcome of that rural atmosphere.